The Concept and Forms of Educational Communication - Eshmuradov Urol Khuzhanovich (Miasto Przyszłości, 2024)
Education reforms have helped change the educational priorities of higher education institutions. The social system requires universities to prepare specialists for competitiveness in the labor market and social and professional mobility. One of the problems of higher education institutions is to train specialists with high professional skills and the desire to open themselves to any type of activity. The article discusses the teacher’s pedagogical activities and his communication style.